2014
DOI: 10.1016/j.bbamem.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the chain length distribution of free fatty acids on the mixing properties of stratum corneum model membranes

Abstract: The stratum corneum (SC) plays a fundamental role in the barrier function of the skin. The SC consists of corneocytes embedded in a lipid matrix. The main lipid classes in the lipid matrix are ceramides (CERs), cholesterol (CHOL) and free fatty acids (FFAs). The aim of this study was to examine the effect of the chain length of FFAs on the thermotropic phase behavior and mixing properties of SC lipids. Fourier transform infrared spectroscopy and Raman imaging spectroscopy were used to study the mixing properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 35 publications
12
54
0
Order By: Relevance
“…16 It was shown that the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 22 observed in Cer24/FFA24-d 47 /Chol mixture suggest a molecular organization allowing unusual motional freedom.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 It was shown that the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 22 observed in Cer24/FFA24-d 47 /Chol mixture suggest a molecular organization allowing unusual motional freedom.…”
Section: Discussionmentioning
confidence: 96%
“…As reference values (measured the same way as the values presented in Figure 6), the splittings of pure Cer20 was found to be 9.8 cm -1 , 41 whereas that of deuterated solid FFA was 8.5 cm -1 . 16 Therefore Cer24/FFA16-d 31 /Chol mixture appears to be forming extensive phase-separated domains, according to its δCD 2 and δCH 2 splitting values. These values are similar to those previously reported for an equimolar mixture of Cer16/FFA16-d 31 /Chol, 14 where δCD 2 and δCH 2 band splittings were found to be 6 cm -1 , and 9.5 cm -1 respectively, indicating that Cer16 and FFA16 formed phaseseparated crystalline domains with orthorhombic chain packing.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, replacement of the stratum corneum long‐chain fatty acids with short‐chain fatty acids from healthy individuals altered the stratified structure of skin tissues, causing skin barrier dysfunction. In contrast, when FFAs in a lipid mixture that simulates skin lipid production were changed from short‐chain FFAs to long‐chain FFAs, the mixture exhibit a more solid structure and higher stability . During analysis of skin lipid variations in patients with AD, van Smeden et al .…”
Section: Influence Of Variations In Lipid Components On the Skin Barriermentioning
confidence: 99%
“…NP LM 32, AG LM 32, and AP LM 32 were prepared by drying chloroform/methanol (2:1, v/v), containing CER [NP]/CHOL/PA (1.3:1.0:1.5, mol%), CER [AG]/CHOL/PA (1.9:1.0:4.3, mol%), CER [AP]/CHOL/PA/SCHOS (8.6:6.1:5.4:1.0, mol%), on respective glass plates at 32 °C. These lipids were chosen to have similar carbon chain lengths because it effects the phase separation of LMs . NP LM 80, AG LM 80, and AP LM 80 were obtained by heating NP LM 32, AG LM 32, and AP LM 32 at 80 °C on heat stage for 30 min, then equilibration at room temperature (r. t.) for more than 30 min, respectively.…”
Section: Methodsmentioning
confidence: 99%